2018
DOI: 10.1124/jpet.118.251371
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Induced Leucine Zipper Promotes Neutrophil and T-Cell Polarization with Protective Effects in Acute Kidney Injury

Abstract: The glucocorticoid-induced leucine zipper (GILZ) mediates antiinflammatory effects of glucocorticoids. Acute kidney injury (AKI) mobilizes immune/inflammatory mechanisms, causing tissue injury, but the impact of GILZ in AKI is not known. Neutrophils play context-specific proinflammatory [type 1 neutrophil (N1)] and anti-inflammatory [type 2 neutrophil (N2)] functional roles. Also, regulatory T lymphocytes (Tregs) and regulatory T-17 (Treg17) cells exert counterinflammatory effects, including the suppression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 62 publications
(74 reference statements)
1
22
0
Order By: Relevance
“…According to the National Health Commission of China's Diagnosis and Treatment of New Coronavirus Pneumonia guidelines [22], glucocorticoids, lopinavir/ritonavir, and ribavirin are treatment options for COVID-19. Interestingly, glucocorticoids provide a renoprotective effect in AKI via glucocorticoidinduced leucine zipper-(GILZ-) induced immunosuppression [66]. In contrast, lopinavir/ritonavir is widely used to treat AIDS and has been reported to cause renal tubular dysfunction and CKD [67].…”
Section: Possible Mechanisms Underlying Comorbid Chronicmentioning
confidence: 99%
“…According to the National Health Commission of China's Diagnosis and Treatment of New Coronavirus Pneumonia guidelines [22], glucocorticoids, lopinavir/ritonavir, and ribavirin are treatment options for COVID-19. Interestingly, glucocorticoids provide a renoprotective effect in AKI via glucocorticoidinduced leucine zipper-(GILZ-) induced immunosuppression [66]. In contrast, lopinavir/ritonavir is widely used to treat AIDS and has been reported to cause renal tubular dysfunction and CKD [67].…”
Section: Possible Mechanisms Underlying Comorbid Chronicmentioning
confidence: 99%
“…Thus, there is a need to identify therapeutic options that can modulate ILC subsets to those of the normal kidney with the objective of conferring beneficial impact to the ischemic-reperfused kidney. In light of our recent demonstration that both cannabidiol and GILZ exert significant renoprotective effects, as reflected by reduction in cell death and improved functional outcomes, in association with similar changes in polarization of neutrophils and T lymphocytes in favor of their regulatory/suppressive phenotypes [16,17], we sought to establish the impact of each agent on the profile of ILC subsets of the kidney subjected to IRI. Interestingly, cannabidiol and GILZ caused similar changes in the profile of ILC subsets in the ischemic-reperfused kidney, restoring their levels towards those of sham-operated kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…in preparation for the surgical procedure which consisted of two flank incisions and clamping of the left renal pellicle, for 20 min, using a nontraumatic vascular clamp while the right kidney served as sham control. Thereafter, the vascular clamp was removed and restoration of renal Journal of Immunology Research blood flow confirmed, visually, prior to closure of muscle and skin layers using 4-0 silk sutures and autoclips, respectively [16,17]; each independent experiment included 3-6 animals, and the number of animals for each group/condition is indicated under Figure legends. Each of the following agents was administered, intraperitoneally in a volume of 50 μl, 10 min before restoration of renal blood flow: (a) vehicle (DMSO), (b) cannabidiol (10 mg/kg, 16), (c) TAT (0.1 mg/kg in PBS), and (d) TAT-GILZ (0.2 mg/kg in PBS); the latter dosage regimen is based on a two-fold larger molecular weight of GST-TAT-GILZ than GST-TAT as well as studies indicating resolution of LPS-induced inflammation in response to TAT-GILZ treatment and its effectiveness in the murine model of acute kidney injury [17,29].…”
Section: Tat and Tat-gilzmentioning
confidence: 99%
See 2 more Smart Citations